Efficacy of vitamin E and selenium supplementation in the prevention and treatment of signal grass (Brachiaria Decumbens Stapf) toxicity in sheep - Muhammad, Ajwad Awad (2011)
Continuous incidence of Brachiaria decumbens intoxication outbreaks arises due to ineffective strategies in treating and preventing its aftermath in the global small ruminant industry. Previous conducted studies focusing on the prevention yielded with limited success. Improved usage of B. decumbens for livestock production requires better approach to reduce losses caused by its toxic effects. In this thesis, studies conducted were based on the principle dogma of using certain antioxidants both in prevention and treatment of B. decumbens intoxication in sheep. Following confirmation of oxidative stress (feeding of B. decumbens alone) in the pathogenesis of this toxicity, the role of vitamin E and selenium combination in preventing and treating toxicity was mounted. A total of 36 local indigenous sheep were used in two sets of experiments. In all experiments, sheep receiving B. decumbens were fed the grass obtained via cut and carry either alone or with vitamin E+selenium 14 days before and in the first day of start feeding or injected subcutaneously with combination of vitamin E+selenium on the 1st and 3rd day of the first clinical sign appearance of B. decumbens intoxication. Classical clinical signs of B. decumbens intoxication were monitored. Blood and pertinent tissues were collected at necropsy. The liver and kidney function tests, pertinent indicators reflecting lipid peroxidation status and antioxidant defenses were assayed. Furthermore, some liver metabolizing enzymes and pathological studies both at cellular and ultrastructural levels were conducted too. Clinical signs of photosensitisation jaundice and submandibular oedema and lesions of hepatocytic necrosis, renal hydropic degeneration and/or coagulative necrosis and brain vacuolations due to status spongiosus of the white matter (demyelination) were noticed in sheep fed B. decumbens alone. An impairment of the antioxidant defense system and involvement of lipid peroxidation was confirmed in all B. decumbens fed sheep except those receiving vitamin E plus selenium either as a prophylaxis or treatment. Obviously, selenium and vitamin E function synergistically to protect against cellular damage by intermediate reactive species. Vitamin E, an integral component of the cell membrane, is in perfect position to disrupt the lipid peroxidation process by quench free radicals capable of initiating and propagating lipid peroxidation such as alkoxy and alkyl peroxy radicals and have been shown to affect the activity and induction of the microsomal P-450. Selenium as an essential constituent of the glutathione peroxidase (Se-GSH-Px) active site reduces hydrogen peroxide, as well as other hydroperoxides to less reactive water and alcohols, respectively. Therefore, the supplementation of vitamin E as α-tocopherol acetate+sodium selenite is effective in blocking the development of B. decumbens intoxication in sheep by potentiating the cells’ ability to cope with oxidative stress and thus block membrane lipid peroxidation that can disrupt cell compartmentalization and function during B. decumbens ingestion. Therapeutically, the conducted study showed that supplementation with vitamin E and selenium is efficacious in alleviating the toxicity of B. decumbens in sheep.